2009
DOI: 10.1136/jnnp.2009.171967
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of recurrent intracranial aneurysms with re-coiling or covered stents

Abstract: Recurrent aneurysms after coiling can be successfully treated and occluded with re-coiling or covered stent placement. However, covered stents seem to be more effective than re-coiling with regard to complete occlusion of recurrent aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…All microcatheter and Willis covered stent insertion procedures were based on our previously described techniques and clinical experience. 16,17 All patients were followed-up for between 3 and 48 months (mean = 20.8 months), and angiograms were performed at 3, 6 and 12 months to assess whether there was occlusion of the fistula, ICA patency, stent stenosis, and pseudoaneurysm formation.…”
Section: Endovascular Techniquementioning
confidence: 99%
“…All microcatheter and Willis covered stent insertion procedures were based on our previously described techniques and clinical experience. 16,17 All patients were followed-up for between 3 and 48 months (mean = 20.8 months), and angiograms were performed at 3, 6 and 12 months to assess whether there was occlusion of the fistula, ICA patency, stent stenosis, and pseudoaneurysm formation.…”
Section: Endovascular Techniquementioning
confidence: 99%
“…Based on previous studies [5-9, 11, 12, 20], we predicted that the complete occlusion rate during the 6-month angiographic follow-up period would be <65% (mean 62.5%) with coil embolization and >90% with the covered stent [26,27]. We estimated that 80-90 patients would need to be enrolled for the study to have a statistical power of 80%.…”
Section: Discussionmentioning
confidence: 98%
“…Our preliminary results with this stent indicate good flexibility and efficacy in cranial internal carotid artery (CICA) aneurysm treatment in patients without an extremely tortuous internal carotid artery (ICA) [26]. We also found that covered stents are more effective than recoiling with respect to the complete occlusion of recurrent aneurysms [27]. Here we present the results of a nonrandomized prospective trial of the endovascular treatment of CICA aneurysms with a covered stent or coil embolization, with the goal of comparing the efficacies of these two treatment approaches.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations